The role of spine length in crustacean and fish associations with echinoids at Los Cabos, Baja California Sur, Mexico - Hayes, Floyd E.; Richards, Sean T.; Robles, Antonio I.; Gouveia, Robert A.; Fayard, Gillund G. (Revista de Biología Tropical, 2022)
Introduction: Echinoids (sea urchins) provide shelter for a variety of facultative or obligatory ectosymbionts. Objective: To evaluate the hypothesis that decapods and fishes prefer to associate with echinoid individuals and species that have longer spines. Methods: We visually studied the frequency of decapod crustaceans and fishes associated with echinoids in shallow water (< 4 m) and deeper water (5-20 m) at Los Cabos, Baja California Sur, Mexico, during 1-6 January 2019. Results: We inspected 1 058 echinoids of six species. Five decapod species associated with three species of echinoids. When compared with other echinoid species, in shallow water, decapods associated 5.1 times more often with the longest-spined echinoid Diadema mexicanum (7.0 times more decapods per individual D. mexicanum); in deeper water, association frequency was similar for all echinoid species. Fourteen fish species associated with four echinoid species. In shallow water, fishes associated 2.6 times more with D. mexicanum (4.5 times more fishes per individual). There was no preferred echinoid species in deeper water. Longer-spined D. mexicanum had more decapods and fishes. Associations were more frequent in shallow water. Multiple individuals and species of decapods and fish often associated together with a single D. mexicanum. The decapod that presumably is Tuleariocaris holthuisi showed a possible obligatory association with one of the equinoids (D. mexicanum); the other decapods and all fish species are facultative associates. Conclusion: Our results support the hypothesis that decapods and fishes associate most frequently with echinoid with the longest spines, presumably to reduce the risk of predation.